2022
DOI: 10.1101/2022.08.07.499047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple pathways for SARS-CoV-2 resistance to nirmatrelvir

Abstract: Nirmatrelvir, an oral antiviral targeting the 3CL protease of SARS-CoV-2, has been demonstrated to be clinically useful in reducing hospitalization or death due to COVID-191,2. However, as SARS-CoV-2 has evolved to become resistant to other therapeutic modalities3-9, there is a concern that the same could occur for nirmatrelvir. Here, we have examined this possibility by in vitro passaging of SARS-CoV-2 in increasing concentrations of nirmatrelvir using two independent approaches, including one on a large scal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 50 publications
(76 reference statements)
0
34
0
Order By: Relevance
“…These mutants are reported to be nirmatrelvir resistant, with K i values increasing between 19.2 to 38.0-fold, therefore corroborating our findings and reflecting the accuracy of our design methodology [ 13 ]. Interestingly, the E166V mutant, experimentally shown to confer the strongest resistance (∼100-fold) [ 23 ], was found to be one of the most plausible resistance-causing mutants in our design experiments ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 91%
“…These mutants are reported to be nirmatrelvir resistant, with K i values increasing between 19.2 to 38.0-fold, therefore corroborating our findings and reflecting the accuracy of our design methodology [ 13 ]. Interestingly, the E166V mutant, experimentally shown to confer the strongest resistance (∼100-fold) [ 23 ], was found to be one of the most plausible resistance-causing mutants in our design experiments ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 91%
“…In a FRET-based assay, the enzymatic activities of recombinant 3CLpro proteins carrying the L50F, E166A and L167F subsstitutions alone or combined proved to be significantly lower, compared to that of the WT protein (16) . In another similar study, in vitro selection of resistant variants against nirmatrelvir resulted in identification of several resistance-associated subsstitutions with the E166V subsstitution resulting in the strongest resistance phenotype (17) . However, this subsstitution at position 166 resulted in loss of the virus replication fitness in vitro that was restored by compensatory subsstitutions such as L50F and T21I (17) .…”
Section: Discussionmentioning
confidence: 97%
“…Two of the selected substitutions (i.e. L50F and L167F) have been reported to be detected (at low frequencies) in SARS-CoV-2 viruses naturally circulating in the population (17). Moreover, the Paxlovid label indicates that the E166V subsititution is among the treatment-emergent substitution, which is more common in nirmatrelvir/ritonavir treated subjects relative to placebo-treated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…During our study, multiple preprints have appeared, discussing certain SARS-CoV-2 M pro mutations and their effect on NTV. [27][28][29][30][31][32][33] The methodologies used in these studies to discover the mutations with resistance potential are diverse, which is reflected in their results. As is observed in our study, previously reported mutational hotspots include the active site of M pro , with special emphasis on the residues S144, E166, L167, and Q192.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several recent preprints disclose experimentally found M pro variants which reduce the potency of NTV. [27][28][29][30][31][32][33] These studies encompassed a variety of methodologies, including data mining of SARS-CoV-2 sequences and passage experiments. Especially substitutions of substrate binding pocket residues such as S144, E166, L167, and Q192 resulted in loss of NTV inhibition (Supporting Information Table 3).…”
Section: Introductionmentioning
confidence: 99%